Hierarchically Porous Wearable Composites for High‐Performance Stretchable Supercapacitors - Jing Han; Bingang Xu; Cuiqin Fang; Juyang Wei; Zihua Li; Xinlong Liu; Yujue Yang; Qian Wang; Junze Zhang (Advanced Science, 2025)
Abstract With the rapid development of wearable electronic devices, the demand for flexible, durable, and high‐performance energy storage systems has increased significantly. Nevertheless, maintaining stable electrochemical performance during stretching while ensuring high stretchability and mechanical stability remains a challenge. Herein, this study proposes a novel type of stretchable supercapacitors made from carbon nanotube (CNT) and styrene‐butadiene‐styrene (SBS) composite scaffolds prepared on pre‐stretched carbon fabrics using the breath figure method. Hydrothermal treatment is then performed to grow NiCo‐LDH at the treated carbon fabrics. This method induces the formation of a hierarchically porous structure under high humidity conditions, controls the hydrothermal growth of NiCo‐LDH in the CNT/SBS composite scaffold, and significantly enhances the electrochemical performance and mechanical stability. The supercapacitor demonstrates remarkable retention of 94% capacitance under 80% tensile strain and sustains a small 8% degradation over 20 000 charge–discharge cycles, achieving a specific capacitance of 4948 mF cm⁻2 at 2 mA cm⁻2. The device has an energy density of 801.6 µWh cm⁻2 (400.6 Wh kg⁻¹) and exhibits excellent performance at a power density of 3.5 mW cm⁻2 (1749.5 W kg⁻¹). These properties make the supercapacitors a potential for next‐generation smart wearables and wearable electronics.